Greendrive EV: an innovative palm oil ester blend for EV transmission fluid - Mustaffha, Samihah; El Pebrian, Darius; Mustafa, Mohd Muhyiddin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The growing adoption of electric vehicles (EVs) has driven significant advancements in sustainable and efficient technologies. This rapid development highlights the increasing need for specialized lubricants designed to enhance EVs performance and durability. The sustainability of EVs closely related to the efficiency and environmental impact of their mechanical systems, including lubricants. Conventional petroleum-based transmission fluids commonly used in internal combustion engine (ICE) vehicles are unsuitable for EVs due to their inability to meet the requirements of electrical insulation properties and environmental sustainability. To address this challenge, an innovative transmission fluid for EVs based on palm oil ester blends has been developed, specifically tailored to meet the special requirements of EV transmissions. The formulation of this product involves blending palm oil ester base oil, mineral base and specialized additives. This innovative approach emphasized on the unique properties of palm oil esters to provide superior lubrication, enhanced thermal stability and reduced wear. Moreover, it improves efficiency and minimize environmental impact. The results demonstrate that the blends of palm oil ester, mineral oil and additives effectively reduce wear rates. Furthermore, this innovation aligns with Sustainable Development Goals (SDGs) by reducing dependency on petroleum-based fluids and promoting the sustainable use of palm oil derivatives. This novel formulation also holds significant socio-economic potential by contributing to circular bioeconomy and supporting palm oil industry stakeholders. GreenDrive EV Transmission Fluid presents a viable solution for eco-conscious manufacturers, by balancing high performance with environmental responsibility. It is specifically designed to meet the needs of automotive OEMs and lubricant manufacturers.